A high speed data acquisition system - Martens, Andrew (Department of Electrical Engineering, 2014)
Digital systems pervade the world around us. The interface between analogue data sources and these digital systems is the realm of analogue to digital converters (ADCs) that acquire digital snap-shots of data for further processing. Some applications require high sampling rates or high resolution data (or both). In addition to this, certain applications require the capture of large amounts of data. A good example of an application requiring a high sampling rate and high resolution data, is a digital spectrum analyser used to analyse large bands of a spectrum and offer precise results. Radar systems such as synthetic aperture radars use post-processing techniques on large quantities of data. A developing field requiring versatile data capture systems is that of software defined radio (SDR). It is a collection of hardware and software technologies that enable reconfigurable system architectures for wireless networks and user terminals. This document gives details on a project to build a high speed, high resolution data acquisition system that is capable of performing to some of the most stringent requirements. Specifically, this thesis documents the design, implementation and testing of firmware implemented in an FPGA in a commercial data capture card as part of the system. This firmware would facilitate the real-time transfer of captured data to RAM in a host PC.